Concentrations of representative uraemic toxins in a healthy versus non-dialysis chronic kidney disease paediatric population. Issue 6 (24th July 2017) - Snauwaert, Evelien; Van Biesen, Wim; Raes, Ann; Glorieux, Griet; Van Bogaert, Valerie; Van Hoeck, Koen; Coppens, Marc; Roels, Sanne; Vande Walle, Johan; Eloot, Sunny
ABSTRACT: Background: Chronic kidney disease (CKD) in childhood is poorly explained by routine markers (e.g. urea and creatinine) and is better depicted in adults by other uraemic toxins. This study describes concentrations of representative uraemic toxins in non-dialysis CKD versus healthy children. Methods: In 50 healthy children and 57 children with CKD Stages 1–5 [median estimated glomerular filtration rate 48 (25th-75th percentile 24–71) mL/min/1.73 m 2 ; none on dialysis], serum concentrations of small solutes [symmetric and asymmetric dimethyl-arginine (SDMA and ADMA, respectively)], middle molecules [β2-microglobuline (β2M), complement factor D (CfD)] and protein-bound solutes [ p -cresylglucuronide (pCG), hippuric acid (HA), indole-acetic acid (IAA), indoxyl sulphate (IxS), p -cresyl sulphate (pCS) and 3-carboxy-4-methyl-5-propyl-furanpropionic acid (CMPF)] were measured. Concentrations in the CKD group were expressed as z -score relative to controls and matched for age and gender. Results: SDMA, CfD, β2M, IxS, pCS, IAA, CMPF and HA concentrations were higher in the overall CKD group compared with controls, ranging from 1.7 standard deviations (SD) for IAA and HA to 11.1 SD for SDMA. SDMA, CfD, β2M, IxS and CMPF in CKD Stages 1–2 with concentrations 4.8, 2.8, 4.5, 1.9 and 1.6 SD higher, respectively. In contrast, pCS, pCG and IAA concentrations were only higher than controls from CKD Stages 3–4 onwards, but only in CKD Stage 5 for ADMA and HA ( z -score 2.6 and 20.2, respectively). Conclusions: This is the first study to establish reference values for a wide range of uraemic toxins in non-dialysis CKD and healthy children. We observed an accumulation of multiple uraemic toxins, each with a particular retention profile according to the different CKD stages.